Specifics of residency training at the medical university in the specialty "General Practice (Family Medicine)" - V. N. Larina; O. V. Saino; M. P. Mikhailusova; M. G. Golovko; E. N. Sheregova; Ch. G. Gudiev (Кардиоваскулярная терапия и профилактика)
Aim. To analyze the specifics of residency training in the specialty 31.08.54 "General practice (Family Medicine)" at the medical university.Material and methods. Theoretical (search and analysis of available full-text articles in the Elibrary database using keywords: residency, general practice, teaching methods, medical university) and verbal-communicative method were used in the form of an online survey of 27 residents using a questionnaire developed in based on Google Forms.Results. During the period from 2018 to the present, 68 residents have been trained in the specialty "General practice (Family Medicine)". The practice-oriented direction of training is important for the majority of residents (77,8%). Theoretical training turned out to be especially interesting and useful for 48,1%, scientific activity — for 7,4% of residents. Among the difficulties, work according to standards (51,9%), working with the patient (14,8%) and interpreting the paraclinical data (11,1%) were noted.Conclusion. The educational process in residency in the specialty "General Practice (Family Medicine)" allows for multifaceted training of future specialists to work in primary healthcare. The department has created conditions for additional development by residents of new skills and abilities for successful work, but our own experience indicates the need for further improvement of the educational process.